2021
DOI: 10.1128/msphere.00543-21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of IS 1216 Carrying Multidrug Resistance Gene Cluster in Serotype III/Sequence Type 19 Group B Streptococcus

Abstract: Most previously isolated group B streptococcus (GBS) strains express either the Srr1 or Srr2 glycoprotein, which plays an important role in bacterial colonization and invasion. These glycoproteins are potential protein vaccine candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…We also detected the aminoglycoside resistance gene aadE. Resistance to aminoglycosides mediated by aadE has been reported for human clinical GBS in the UK [33], South Korea [34], and China [35], and for bovine mastitis isolates belonging to the species Staphylococcus aureus [36]. To our knowledge, it has not been described in bovine GBS previously.…”
Section: Discussionmentioning
confidence: 74%
“…We also detected the aminoglycoside resistance gene aadE. Resistance to aminoglycosides mediated by aadE has been reported for human clinical GBS in the UK [33], South Korea [34], and China [35], and for bovine mastitis isolates belonging to the species Staphylococcus aureus [36]. To our knowledge, it has not been described in bovine GBS previously.…”
Section: Discussionmentioning
confidence: 74%
“…An examination of ARGs and selected virulence factors (VFs) in S. aureus sequence data showed that six ARGs were frequently found in pig farm isolates (pig farm‐associated ARG [PFA‐ARGs]), fexA (phenicols ARG), [ 29 ] lnuB (lincosamides ARG), [ 30 ] dfrG (trimethoprim ARG), [ 31 ] tetL (tetracyclines ARG), [ 32 ] aac6‐Aph2 , and spw (aminoglycosides ARGs); [ 33 , 34 ] and three VFs frequently found in hospital isolates (hospital‐associated VFs [HA‐VFs]), scn ( Staphylococcal complement inhibitor), [ 35 ] sak (staphylokinase), [ 35 ] and sprD (small pathogenicity island RNAs) [ 36 ] (Figure S2 , Supporting Information). The differences in PFA‐ARGs and HA‐VFs compared using a Fisher's exact test ( p ‐value is <0.00001) (Table S5 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of HLGR resistance in GBS is mediated by the chromosomally integrated transposon Tn3706 (a derivative of enterococcal Tn5281 or staphylococcal Tn4001) or plasmid pIP501 [ 12 , 14 , 29 , 30 , 34 , 35 , 36 , 37 ]. Nevertheless, the HLGR rate in GBS is rarely reported, although probably underestimated due to the absence of international guidelines on HLGR susceptibility testing for GBS.…”
Section: Discussionmentioning
confidence: 99%
“…One representative isolate analyzed by whole-genome sequencing revealed the presence of four large novel cluster sites. Specifically, site 4 in the srr1 gene locus was replaced by an lsa ( E ) -lnu ( B ) -aadK-aac-aph-aadE -carrying multidrug-resistant gene cluster flanked by two IS1216 transposases with 99% homology to the enterococcal plasmid pKUB3007-1 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%